KARAKTERISTIK FISIKO-KIMIA TEPUNG UBI JALAR (Ipomoea batatas) VARIETAS SUKUH DENGAN VARIASI PROSES PENEPUNGAN [Physico-Chemical Characteristics of Sukuh Variety Sweet Potatoes (Ipomea batatas) Flours Made with Various Methods] - Elvira Syamsir; Trifena Honestin (Jurnal Teknologi dan Industri Pangan, 2009)
Sweet potato has considerable potencies to support food diversification program based on flour and starch product. Various processing  methods  in the flour processing show great effect on alteration of the physicochemical properties of sweet potato flour. This research investigated the effects of different flour processing methods on the physicochemical properties of sweet potato flour. The results showed that processing method had a significant effect on water content, bulk density, colour (L, a, b), microscopic properties of starch granule, water absorption index, water soluble index and pasting properties of the sweet potato flour.